(untitled) (Research, Society and Development, 2021)
Objectives: To identify and analyze the existing evidence regarding the use of low-intensity light therapy in wound healing. Method: Integrative review based on the Ganong framework, with a search conducted in March 2020, with a period from January 2015 to March 2020. Results: 15 studies were selected, with different research designs. There was a difference in the parameters used with energies ranging from 1 to 20 J, the wavelength between 632.8 and 940 nm and power from 1.08 mW to 6W. Conclusions: There is no established clinical protocol for wound healing using low intensity light therapy; it is observed that there are beneficial effects of photobiomodulation with adequate wavelength, energy density and power of the device. Further studies are needed to better understand this therapy and establish clinical protocols in health practice.